Modelo de gestión de la producción para mejorar la eficiencia de fabricación de crisoles aplicando técnicas de lean manufacturing: caso del sector manufactura - Albujar Arriola, Daniela Karina (2025)
The present research refers to the study of a manufacturing company located in the city of Lima, Peru, and has the objective of developing a production management model to improve the efficiency of the manufacture of refractory crucibles. The company started operations seven years ago and has about 15 employees in the administrative and operational areas. Currently, the efficiency of the production process is 62%, below the industry average of 75%, showing a gap of 13%. The main causes of this problem are: a) unproductive times caused by unplanned stoppages due to failures and numerous calibrations; b) reprocesses due to lack of standardized work in the process of mixing chamotte from pulverized refractory material, clay and binders. Lean Manufacturing and specifically TPM, SMED and Standardized Work were used as solution techniques, achieving an improvement in the OEE from 69% to 85%, the reduction in the die change time of the hydraulic press from 104 minutes to 40.5 minutes, in addition to reducing the amount of reprocessed mixture from 29% to 5%. By means of process simulation, it was demonstrated that it is possible to improve the efficiency in the production of refractory crucibles from 62% to 71%; meaning an excellent contribution by applying engineering techniques for the improvement of industrial processes.